Model-assisted analysis on the response of tomato fruit growth to source-sink ratio regulated by water and nitrogen - Huiping Zhou; Jinliang Chen; Shaozhong Kang (Agricultural Water Management)
Water and nitrogen (N) are essential factors affecting the tomato plant-fruit system. However, little is known about to what extent water and N could regulate the water and carbon fluxes between the source-sink system, thus influencing fruit growth. In this study, the source-sink ratio (Rss) was proposed and then related to water and N supply by a WN-Jensen function, according to the experimental observations from tomatoes grown under various water and N conditions. A process-based model was applied to investigate the effects of water and N supply on fruit growth through modifying one of the major model inputs, the sucrose concentration in phloem solution (Cp), which was assumed to be proportional to Rss. The model was then assessed with the data sets from tomatoes grown under different water and N conditions. The results showed that, N deficit and water stress at fruit early /whole growth stage had significant limitation on plant and fruit growth, together with low stem water potential and water consumption. The dynamics of fruit growth were better simulated by the model when the effects of water and N on source-sink regulation were taken into consideration through modifying Cp. Compared to the original model simulation, MAE and RRMSE of fruit growth prediction decreased by up to 82.0 % and 79.9 %. The simulation efficiency of fruit fresh and dry weights was in the range of 77.4 %-96.4 % and 72.9 %-92.9 % by the modified model, respectively. Model-assisted analysis showed that water supply could be reduced by 11.9 %, 27.0 % and 41.1 % at fruit early, middle and late stage together with a reduction of 27.5 % N application (saving investment of 131 $/ha), while ensuring the same fruit growth by considering water and nitrogen regulation on source-sink relation.